Investigation of flow past various shape bluff bodies at low reynolds number - Dobriyal, Ritvik (2016)
Two-dimensional flow over bluff bodies of different shapes is studied in the laminar regime. Different shapes are created by altering the rear part of a circular cylinder where flow separation occurs. In order to create a more streamlined body, the rear portion of a circular cylinder is changed from that of a circular arc to an elliptical one with semi major axis greater than the radius of circle, and less than radius of circle for making a more bluff body. Flow is studied by performing a numerical simulation using commercially available CFD package called FLUENT. It is found that the variation with Reynolds number of bluff body characteristics like lift, drag and Strouhal number is similar to that of a circular cylinder. Critical Reynolds number at which the vortex shedding begins, is also found to increase with extending shape. As the body is extended to become more streamlined, lift fluctuations, drag and shedding frequency begin to fall. However, their variation do not follow a similar pattern for all shape changes. The shape change is quantified by defining a shape factor. Variation of the coefficient of lift and Strouhal number is linear with shape factor. However, the sensitivity of lift force to body shape is dependent on Reynolds number, while the sensitivity of the Strouhal number is independent of it. Variation of the drag force on the other hand varies with shape factor according to power law. Using these relations, lift and drag force, as well as Strouhal number are expressed as functions of shape factor and Reynolds number.